2016
DOI: 10.1063/1.4966644
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Evidence of halogen bonds in clathrate cages

Abstract: We present a theoretical characterization of the interaction of Cl and Br in the 5 and 56 clathrate cages, respectively, based on energy partitioning analysis and a study of the electronic shifts associated with transitions to the main valence bands. Our analysis clearly shows that while Br@56 does not show halogen bonding interactions in its equilibrium geometry, Cl@5 presents all the characteristics expected for halogen bonding. This is accomplished by the interaction of the usual sigma-hole with the lone pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 31 publications
3
44
0
Order By: Relevance
“…The geometries for the clathrate complexes have been taken from those reported in a previous local correlation study where evidence of halogen bonding was found for the Cl2 @512 cage in the global energy minimum but not in Br2 @512612 , where it appeared at a geometry which does not correspond to a total energy minimum. Using the local correlation energy partitioning analysis in this case, it was possible to establish a clear correlation with the ionic energy component and for this reason the geometry at which this component is minimum is also presented and discussed.…”
Section: Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…The geometries for the clathrate complexes have been taken from those reported in a previous local correlation study where evidence of halogen bonding was found for the Cl2 @512 cage in the global energy minimum but not in Br2 @512612 , where it appeared at a geometry which does not correspond to a total energy minimum. Using the local correlation energy partitioning analysis in this case, it was possible to establish a clear correlation with the ionic energy component and for this reason the geometry at which this component is minimum is also presented and discussed.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In contrast the much larger blue‐shifts observed in bromine aqueous solutions were consistent with the formation of halogen bonding interactions . However evidence of halogen bonding in clathrate cages was strongly suggested in ab initio local correlation calculations through an energy partitioning analysis and calculation of the electronic shifts at selected geometries . In particular the role of the ionic component as indicator of halogen bonding was stressed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A simple electrostatic model of the clathrate hydrate cage predicts a blue shift in the UV-visible spectra, which agrees with experiment. Ochoa-Resendiz, BatistaRomero, and Hernandez-Lamoneda [70] in 2016 employed ab initio calculations and natural bond order analysis to investigate Cl 2 and Br 2 guests in various clathrate hydrate host sites. The picture that emerges is that of an interaction between the lone pair of the nearest oxygen atom in the clathrate hydrate host with the sigma LUMO of the halogen dimer X 2 but only when the halogen is out of its central equilibrium position in the cage, thus allowing a significant cage-halogen interaction.…”
Section: Solidificationmentioning
confidence: 99%